2011
DOI: 10.1016/j.molcel.2011.02.031
|View full text |Cite
|
Sign up to set email alerts
|

ERK-MAPK Drives Lamellipodia Protrusion by Activating the WAVE2 Regulatory Complex

Abstract: Summary Cell movement begins with a leading edge protrusion, which is stabilized by nascent adhesions and retracted by mature adhesions. The ERK-MAPK (extracellular signal regulated kinasemitogen-activated protein kinase) localizes to protrusions and adhesions, but how it regulates motility is not understood. We demonstrate ERK controls protrusion initiation and protrusion speed. Lamellipodial protrusions are generated via the WRC (WAVE2 Regulatory Complex), which activates the Arp2/3 actin nucleator for actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
200
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(215 citation statements)
references
References 51 publications
(86 reference statements)
12
200
3
Order By: Relevance
“…Indeed, the recruitment of Shp2 to the plasma membrane was found to promote the dephosphorylation of Rho kinase II (ROCKII), resulting in modulation of RhoAinduced cell rounding (41). Based on the known roles of the Ras/ MAPK pathway in cell motility in diverse systems (42), these findings indicate that RSK likely regulates the involvement of Shp2 in both of these pathways to promote a change in cell shape and cell motility.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the recruitment of Shp2 to the plasma membrane was found to promote the dephosphorylation of Rho kinase II (ROCKII), resulting in modulation of RhoAinduced cell rounding (41). Based on the known roles of the Ras/ MAPK pathway in cell motility in diverse systems (42), these findings indicate that RSK likely regulates the involvement of Shp2 in both of these pathways to promote a change in cell shape and cell motility.…”
Section: Discussionmentioning
confidence: 95%
“…These localization determinants may include RhoA and Cdc42; it is suggested that during PBE, Cdc42 drives dynamic F-actin through the Arp2/3 complex, which causes membrane protrusion, and RhoA drives stable F-actin, which restricts this protrusion and exerts constriction at cleavage furrow (Zhang et al, 2008;Maddox et al, 2012). Activation of Arp2/3 during lamellipodial protrusion involves ERK-MAPK activity (Mendoza et al, 2011), and a recent study shows that the Mos-MAPK pathway triggers Arp2/3 activity during spindle movement to the cortex (Chaigne et al, 2013), thus regulation of Arp2/3 during PBE by the Mos-MAPK pathway is also possible. Since regulation of Arp2/3 and Dia might involve Cdc42 and RhoA, respectively, it would be interesting to examine whether active RhoA and active Cdc42 localizations during PBE are regulated by the Mos-MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although these experiments clearly showed that the phosphorylation of Abi1 Ser-216 is increased at the onset of mitosis, they could not exclude the possibility that a basal phosphorylation of Ser-216 may also occur in interphase cells at a level too low to be detected by our antibody. Indeed, using a combination of affinity purification and mass spectrometry analysis, the phosphorylation of serine 216 in Abi1 has been identified in both serumstarved and EGF-stimulated A-431 cells and possibly other cells as well (15,19), suggesting its basal phosphorylation in interphase cells.…”
Section: Discussionmentioning
confidence: 99%